The design and development of the i-Jury management system / Mohamad Rahimi Mohamad Rosman ...[et al.] - Mohamad Rosman, Mohamad Rahimi; Abdullah, Nurulannisa; Arshad, Izzatil Husna; Md. Saleh, Mohamad Sayuti; Mohd Zawawi, Mohd Zafian; Fadzil, Faizal Haini (Universiti Teknologi MARA, 2021)
Handling an event requires a repetitive and complex task, from initial preparation until its conclusion. One of the important elements in an innovation event is the jurying process. The jurying process usually involves tasks with higher priority and must be completed in a limited duration, usually within 4 to 5 days. The inexistence of inexpensive jurying information systems leads to the development of the i-Jury management system (i-Jury). The i-jury management system was developed based on PHP programming language, MySQL database, and jQuery. The development of the information system follows the System Development Lifecycle methodology. The findings show that the development of the information system speeds up the process of managing jury, project management, as well as speeding up the disbursement of results, comparing to previous traditional evaluation methods